Impact of a prescriber and patient educational intervention on discharge analgesia prescribing and hospital readmission rates following elective unilateral total hip and knee arthroplasty. Issue 3 (1st August 2022) - Wood, Daniel; Moy, Shuh Fen; Zhang, Shiran; Lightfoot, Nicholas
Abstract : Introduction: Pain management after elective, unilateral total hip and knee arthroplasty (THA and TKA) should use a multimodal approach. At discharge, challenges include ensuring correct prescribing practices to optimise analgesia and rationalise opioid use as well as ensuring patients are adequately educated to take these medications safely and effectively in the community. This audit cycle reports on a prescriber and patient education intervention using printed guidelines, educational outreach and prescription standardisation along with a patient information sheet to address the high unplanned readmission rate following THA and TKA at our institution. Methods: Two cohorts of patients were identified before (2016) and after (2019) the introduction of the educational package. The primary outcome was the unplanned hospital readmission rate in the 42 days following discharge. Secondary outcomes were the compliance with the set prescribing standards and the prescription of strong opioid medications (morphine or oxycodone) on discharge. Results: There was a reduction in the readmission rate from 20.4% to 10.0% (p=0.004). Readmission rates for pain and constipation were also reduced. The prescribing of tramadol (p<0.001) and non-steroidal anti-inflammatory drugs (p<0.001) both increased while the number of patients who received a strong opioid at discharge decreased (p<0.001) as did the number of patients who received a sustained release strong opioid (p<0.001). Conclusion: We have observed significant improvement in discharge prescribing which coincided with a reduction in unplanned readmissions after elective TKA and THA. Our approach used prescriber guidelines, education and standardisation with printed information for patients to enhance understanding and recall.